The Influence Of Ability And Innovation On Performance Coffee Marketing - Sulastini, Sulastini; Maskur, Maskur; Husnurrofiq, Husnurrofiq (Kontigensi : Jurnal Ilmiah Manajemen, 2025)
The long-term objectives of previous research that have focused on the problems of Product Innovation and Information Technology in manufacturing companies, service companies, research conducted in companies including Anttila J., Jussila K., 2018, Ramayah T., While in this study focuses on the study of Product Ability and Innovation on Coffee Marketing performance carried out in Banjarmasin UMKM. Specific targets to be achieved. Against the backdrop of current Marketing Performance, many problems arise related to employment, especially the performance of UMKM Marketing, therefore problems related to performance need to be resolved. Focus on two problems, namely Analyzing and knowing the Effect of Ability and Innovation partially on UMKM Performance. (1) Is there an effect of Ability on Marketing performance, and (2) Is there an effect of Innovation on Marketing performance. This research method uses a quantitative approach. The data collection technique uses a questionnaire (questionnaire), Population and sample of 48 respondents, while data analysis uses Smart PLS. The Data Analysis Technique used in this study is PLS-SEM because it aims to test the predictive relationship between constructs by seeing whether there is a relationship or influence between the constructs. proposed activities. The study aims to provide the ability that better interactions and relationships are actually side effects of providing space for MSMEs for Coffee Marketing, innovating and still being able to accommodate existing problems.